Factors affecting gross domestic savings in Malaysia / Mohamad Haafizh Faaiz Rosli - Rosli, Mohamad Haafizh Faaiz (Faculty of Business and Management, 2020)
The main objective of this study is to investigate the significant relationship between macroeconomic variables (more specifically inflation rate, unemployment rate, consumption and interest rate) with gross domestic savings in Malaysia. The data were collected annually and the period begins from 1983 to 2017. Ordinary Least Square regression method is practiced to evaluate the regression. E-Views program is being used to determine the econometric problems. The result has shown that there is a significant between macroeconomics variables towards Gross Domestic Saving. I hope that this study could give benefits and answers to know what factors that affect and make the Gross Domestic Saving rate reduced. Therefore, this study as well as will help an individual or family become financially secure in the future.